2020
DOI: 10.11591/ijece.v10i3.pp2484-2502
|View full text |Cite
|
Sign up to set email alerts
|

Applying the big bang-big crunch metaheuristic to large-sized operational problems

Abstract: In this study, we present an investigation of comparing the capability of a big bang-big crunch metaheuristic (BBBC) for managing operational problems including combinatorial optimization problems. The BBBC is a product of the evolution theory of the universe in physics and astronomy. Two main phases of BBBC are the big bang and the big crunch. The big bang phase involves the creation of a population of random initial solutions, while in the big crunch phase these solutions are shrunk into one elite solution e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…To get better prediction, the paper proposed the addition of integrating methods for sampling and learning processes dependent on cost with standard random forests (SRF). They also reported that IRBF produces more accuracy than other algorithms like artificial neural network, decision trees, despite its superior results in other fields [9]- [21].…”
Section: Related Workmentioning
confidence: 99%
“…To get better prediction, the paper proposed the addition of integrating methods for sampling and learning processes dependent on cost with standard random forests (SRF). They also reported that IRBF produces more accuracy than other algorithms like artificial neural network, decision trees, despite its superior results in other fields [9]- [21].…”
Section: Related Workmentioning
confidence: 99%
“…This section discusses how meta-heuristic algorithms [29], [67]- [70], [73]- [75], [82], [90], [95], [109], [119], [160], [163], [176], [179]- [188] are included in the fuzzy modelling process. The implementation of fuzzy meta-heuristic algorithms is depicted in Figure 6.…”
Section: Fuzzy Meta-heuristic Algorithmsmentioning
confidence: 99%
“…The Hopfield neural network was proposed by Hopfield and Tank [14] with both discrete and continuous modes, and it has been widely used in various applications, including identification [15], pattern recognition, and optimization [16]. The continuous Hopfield neural network (CHN) has also demonstrated its ability to solve hard optimization problems [17], [18]. Our main objective in this paper is to adapt the weights and settings of the continuous Hopfield neural network to be able to solve FCSP.…”
Section: Introductionmentioning
confidence: 99%